Essential stem cell methods - Lanza, R. P. (Robert Paul), 1956-; Klimanskaya, Irina; Safari eBooks (Oxford, U.K. ; Burlington, Mass. : Academic Press, 2009)
"This is a fast moving field and these detailed methods will help drive advances in stem cell research. The editors have hand-selected step-by-step methods from researchers with extensive reputations and expertise"--Resource description page.
Neural stem cells: isolation and characterization / Rodney L. Rietze and Brent A. Reynolds -- Neural stem cells and their manipulation / Prithi Rajan and Evan Snyder -- Retinal stem cells / Thomas A. Reh, Joseph A. Brzezinski IV, and Andy J. Fischer -- Dental pulp stem cells / He Liu, Stan Gronthos, and Songtao Shi -- Mouse spermatogonial stems cells: culture and transplantation / Jon M. Oatley and Ralph L. Brinster -- Stem cells in the adult lung / Xiaoming Liu, Ryan R. Driskell, and John F. Engelhardt -- Pancreatic cells and their progenitors / Seth J. Salpeter and Yuval Dor -- Pluripotent stem cells from germ cells: derivation and maintenance / Candace L. Kerr, Michael J. Shamblott, and John D. Gearhart -- Pluripotent stems cells from amniotic fluid and placenta / Dawn M. Delo ... [et al.] -- Hematopoietic stem and progenitor cells from cord blood: Hal E. Broxmeyer ... [et al.] -- Hematopoietic stem cells from bone marrow: purification and functional analysis / K. K. Lin and M. A. Goodell -- Microarray analysis of stem cells and their differentiation / Howard Y. Chang, James A. Thomson and Xin Chen -- Tissue engineering using adult stem cells / Daniel Eberli and Anthony Atala -- Tissue engineering using mesenchymal stem cells / Jeremy J. Mao and Nicholas W. Marion -- Mouse embryonic stem cells / Andras Nagy and Kristina Vintersten -- Human embryo culture / Amparo Mercader, Diana Valbuena, and Carlos Sim(acute)on -- Human embryonic stem cells: derivation and maintenance / Hidenori Akutsu, Chad A. Cowan, and Douglas Melton -- Human embryonic stem cells: characterization and evaluation / Chunhui Xu -- Human embryonic stem cells: feeder-free culture / Michal Amit and Joseph Itskovitz-Eldor -- Neural stem cells, neurons, and glia from embryonic stem cells / Steven M. Pollard, Alex Benchoua, and Sally Lowell -- Hematopoietic cell differentiation from embryonic stem cells / Malcolm A. S. Moore, Jae-Hung Shieh, Gabsang Lee -- Cardiomyocyte differentiation from embryonic stem cells / X. Yang ... [et al.] -- Insulin-producing cells from mouse embryonic stem cells / Insa S. Schroeder ... [et al.] -- Transgene expression and RNA interference in embryonic stem cells / Holm Zaehres and George Q. Daley -- Lentiviral vector-mediated gene delivery into human embryonic stem cells / Michal Gropp and Benjamin Reubinoff -- Engineering embryonic stem cells with recombinase systems / Frank Schn(uml)utgen ... [et al.] -- Tissue engineering using embryonic stem cells / Shahar Cohen, Lucy Leshanski and Joseph Itskovitz-Eldor.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Stem cells -- Research -- Methodology; Electronic books